2019
DOI: 10.1016/j.celrep.2019.01.045
|View full text |Cite
|
Sign up to set email alerts
|

The Neonatal and Adult Human Testis Defined at the Single-Cell Level

Abstract: SUMMARY Spermatogenesis has been intensely studied in rodents but remains poorly understood in humans. Here, we used single-cell RNA sequencing to analyze human testes. Clustering analysis of neonatal testes reveals several cell subsets, including cell populations with characteristics of primordial germ cells (PGCs) and spermatogonial stem cells (SSCs). In adult testes, we identify four undifferentiated spermatogonia (SPG) clusters, each of which expresses specific marker genes. We identify protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
391
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 267 publications
(417 citation statements)
references
References 62 publications
24
391
0
2
Order By: Relevance
“…To validate newly-identified noncanonical primate markers expressed by SPG1 and SPG2 undifferentiated spermatogonia (TCF3, MAGEB2, CDK17, MORC1, DNAJB6, PIWIL4 and FMR1), we co-stained with UCHL1, a broad undifferentiated spermatogonia marker ( Figure 3A-D, S3A-E, upper panels ), or CKIT, a differentiating spermatogonia marker ( Figure 3A-D, S3A-E, lower panels) in human testes tissue. TCF3 and PIWIL4 have been described in previous papers 22,23,28 , while MAGEB2, CDK17, MORC1, DNAJB6, and FMR1 are new markers described in this study. Consistent with our scRNAseq data predictions, our protein markers exhibit overlap with UCHL1+ spermatogonia cells lining the basement membrane of the human testis ( Figure 3A-D, upper panels ), but less overlap with cKIT+ differentiating spermatogonia ( Fig 3A-D, lower panels ); confirming that SPG1 and SPG2 are undifferentiated spermatogonial cell populations.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…To validate newly-identified noncanonical primate markers expressed by SPG1 and SPG2 undifferentiated spermatogonia (TCF3, MAGEB2, CDK17, MORC1, DNAJB6, PIWIL4 and FMR1), we co-stained with UCHL1, a broad undifferentiated spermatogonia marker ( Figure 3A-D, S3A-E, upper panels ), or CKIT, a differentiating spermatogonia marker ( Figure 3A-D, S3A-E, lower panels) in human testes tissue. TCF3 and PIWIL4 have been described in previous papers 22,23,28 , while MAGEB2, CDK17, MORC1, DNAJB6, and FMR1 are new markers described in this study. Consistent with our scRNAseq data predictions, our protein markers exhibit overlap with UCHL1+ spermatogonia cells lining the basement membrane of the human testis ( Figure 3A-D, upper panels ), but less overlap with cKIT+ differentiating spermatogonia ( Fig 3A-D, lower panels ); confirming that SPG1 and SPG2 are undifferentiated spermatogonial cell populations.…”
Section: Resultssupporting
confidence: 61%
“…In order to functionally characterize the colonization potential of the SPG1 population, we enriched for these cells by FACS using the SPG1 cell surface marker TSPAN33 ( Figure 2E, Figure 3J ) that was also described in the human undifferentiated spermatogonia clusters of two previous studies 22,23 . Unsorted, TSPAN33-negative, and TSPAN33-positive cells were xenotransplanted into recipient nude mice ( Figure 3I-J ).…”
Section: Resultsmentioning
confidence: 99%
“…Because our study focuses on representative stages, it will be important to further dissect these mechanisms in order to fully understand the complex and well-coordinated nature of spermatogenesis. Recent studies using single cell analyses have revealed new details on the shifting, transitory transcriptomic and epigenomic environments of progressive cell types in human and mouse spermatogenesis 5459 . Such dynamism is achievable through the functional interplay of complex combinations of TFs and enhancers, as well as other regulatory elements.…”
Section: Discussionmentioning
confidence: 99%
“…MAGE-B2 was also shown to be enriched in spermatogonia in human testis by single cell RNAsequencing (Guo et al, 2018;Sohni et al, 2019;Xia et al, 2020).…”
Section: The Mouse Ortholog Of Human Mage-b2 (Mage-b4) Regulates Stemmentioning
confidence: 97%